Performance Evaluation of Routing Metrics in the LOADng Routing Protocol - Sobral, J.V.V.; Rodrigues, J.J.P.C.; Kumar, N.; Zhu, C.; Ahmad, R.W. (Croatian Communications and Information Society, 2017)
LOADng (Lightweight On-demand Ad hoc Distance-vector Routing Protocol-Next Generation) is an emerging routing protocol that emerged as an alternative to RPL (IPv6 Routing Protocol for Low power and Lossy Networks). Although some work has been dedicated to study LOADng, these works do not analyze the performance of this protocol with different routing metrics. A routing metric is responsible for defining values for paths during the route creation process. Moreover, based on these metrics information a routing protocol will select the path to forward a message. Thus, this work aims to realize a performance assessment study considering different routing metrics applied to LOADng. The scenarios under study consider different traffic patterns and network sizes. The routing metrics are evaluated considering the packet delivery ratio, average energy spent per bit delivered, average latency, and number of hops. The results reveals that routing metrics used by this protocol may influence (directly) the network performance.